Review of Pulmonary Manifestations in Antisynthetase Syndrome - Ghanbar, Mohammad I.; Danoff, Sonye K. (Seminars in Respiratory and Critical Care Medicine, 2024)
Antisynthetase syndrome (ASyS) is now a widely recognized entity within the spectrum of idiopathic inflammatory myopathies. Initially described in patients with a triad of myositis, arthritis, and interstitial lung disease (ILD), its presentation can be diverse. Additional common symptoms experienced by patients with ASyS include Raynaud's phenomenon, mechanic's hand, and fever. Although there is a significant overlap with polymyositis and dermatomyositis, the key distinction lies in the presence of antisynthetase antibodies (ASAs). Up to 10 ASAs have been identified to correlate with a presentation of ASyS, each having manifestations that may slightly differ from others. Despite the proposal of three classification criteria to aid diagnosis, the heterogeneous nature of patient presentations poses challenges. ILD confers a significant burden in patients with ASyS, sometimes manifesting in isolation. Notably, ILD is also often the initial presentation of ASyS, requiring pulmonologists to remain vigilant for an accurate diagnosis. This article will comprehensively review the various aspects of ASyS, including disease presentation, diagnosis, management, and clinical course, with a primary focus on its pulmonary manifestations.
Keywords: antisynthetase syndrome; antisynthetase antibodies; interstitial lung disease; idiopathic inflammatory myopathies; connective tissue disease; idiopathic interstitial pneumonia